Impulse Purchase Behaviour on The Shopee Platform and The Role of Real-Time Commerce Marketing - Dedi Iskamto; Ravi Irfandy Gunawan (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
The objective of this research is to investigate the potential correlation, encompassing good and negative aspects, between individuals' purchasing decisions and Live Commerce events, which are presently prevalent among the Indonesian population. The present study used survey methodology to collect data from participants through the use of structured questionnaires, employing a quantitative research strategy. The research study is comprised of a sample size of 400 persons. The researcher employs a cross-sectional methodology. The data analysis technique employed in this study is descriptive analysis, utilising the SmartPLS 4 software. The research findings suggest that there is a notable and favourable impact of various factors, namely Anchor characteristic, Online Comment, Logistic Service Quality, and Promotion Incentive Information, on the perception of trust. Additionally, the findings also indicate that Anchor characteristic, Logistic Service Quality, and Promotion Incentive Information have a positive influence on the perceived value. Furthermore, the mediator Perceived Trust and Value has a beneficial impact on Impulse Buying Behaviour.